L’art sacré en lumière - Viviana Gobbato (In Situ)
The use of natural light in Christian architecture has a spiritual meaning founded on a long tradition. But over the past fifty years electric lighting has radically altered the way pieces of religious art are now displayed in church architecture. Based on the study of three projects undertaken recently in sacred places—the chapel of Queen Theodelinda at Monza (2015), the Scuola Grande di San Rocco, at Venice (2018) and St Peter’s basilica at Rome (2018)—this article examines the intentions of new lighting strategies using LED lamps and their impact on the presentation and experience of architecture and sacred art in places of heritage. The results show three processes at work: 1) patterning and focusing 2) flexibility of the luminous scenes and 3) quality rendering of colours and materials. These strategies are based on demonstrative functions (showing the space and of the work of art, visual restoration), on cognitive ones (construction of meaning, narration) and aesthetic ones (stimulation of states of sensitivity and contemplation). The lighting techniques which are employed seem to belong to a museology of the senses and are close to systems of sensorial luminous mediation. In the future, this could serve as an inspiration for the promotion and interpretation of the heritage and of heritage collections in museums.